Dual immune modulation of microglia in viral encephalitis: current understanding and future perspectives - Zong, Li; Chen, Pei; Shi, Jing; Chen, Huijie; Lin, Wenwen; Ou, Guanyong; Chen, Xuxiang (Frontiers in Molecular Biosciences, 2025)
Viral encephalitis, characterized by inflammation of the brain parenchyma, poses a significant threat to public health due to its high rates of morbidity and mortality. Microglia, the central nervous system’s resident immune cells, are crucial in the pathophysiology and development of this condition. These microglia exhibit a dual function, being involved in both neuroprotection and neurotoxicity during viral encephalitis. To address this complex interplay, targeted therapeutic strategies that modulate microglia activation state have emerged as a promising approach. These strategies aim to either inhibit excessive microglia activation or promote their neuroprotective functions. By targeting microglia, these therapies hold the potential to improve outcomes for patients with viral encephalitis. This review synthesizes current evidence revealing that microglial responses during viral encephalitis exhibit context-dependent heterogeneity that extends beyond traditional M1/M2 paradigms. Critically, our review reveals a significant translational gap, with no current clinical trials investigating microglial-targeted therapies for viral encephalitis despite promising preclinical evidence. This review provides a comprehensive framework for understanding microglial complexity in viral encephalitis and establishes research priorities for advancing these insights toward clinical application.